EspF of Enterohemorrhagic Escherichia coli Enhances Apoptosis via Endoplasmic Reticulum Stress in Intestinal Epithelial Cells: An Isobaric Tags for Relative and Absolute Quantitation-Based Comparative Proteomic Analysis - Wang, Xiangyu; Yan, Kaina; Fu, Muqing; Liang, Song; Zhao, Haiyi; Fu, Changzhu; Yang, Lan; Song, Zhihong; Sun, Dayong; Wan, Chengsong (Frontiers in Microbiology, 2022)
There have been large foodborne outbreaks related to Enterohaemorrhagic Escherichia coli (EHEC) around the world. Among its virulence proteins, the EspF encoded by locus of enterocyte effacement is one of the most known functional effector proteins. In this research, we infected the HT-29 cells with the EHEC wild type strain and EspF-deficient EHEC strain. Via the emerging technique isobaric tags for relative and absolute quantitation (iTRAQ), we explored the pathogenic characteristics of EspF within host cells. Our data showed that the differences regarding cellular responses mainly contained immune regulation, protein synthesis, signal transduction, cellular assembly and organization, endoplasmic reticulum (ER) stress, and apoptosis. Notably, compared with the EspF-deficient strain, the protein processing in the ER and ribosome were upregulated during wild type (WT) infection. Our findings proved that the EspF of Enterohemorrhagic Escherichia coli induced ER stress in intestinal epithelial cells; the ER stress-dependent apoptosis pathway was also activated within the host cells. This study provides insight into the virulence mechanism of protein EspF, which will deepen our general understanding of A/E pathogens and their interaction with host proteins.